Historia/Historia en Nueva España/México (1750-1850) - Zermeño, Guillermo (El Colegio de México, A.C., 2011)
This paper homeage to the pioneer work of Reinhart Koselleck by borrowing the title of this essay  historia/Historia (history/History) (1975). From thhis starting point, we seek to examine the origins of modern historiography in our country in relation to the emergence of the "modern regime of historicity" (Hartog). We thus explore the historical-lingustic conditions that made way for the rise and development of a new form and function of historical discourse, evisaged from the obervation of the semantic transformation of the term history. Almost a neologism -since it is an anciet word-, History (with a capital H) was the result of the creation of a new space of expierence, both intellectually and politically connoted. Thus, in the light of the Koselleckian antecedent, this essay inquires into the way in which the concept of history changed in the transition from the Novohispanic to the "Mexican" or republican regime.